A fully coupled Hydraulic Mechanical Chemical approach applied to cementitious material damage due to carbonation - Adrien Socié; Nicolas Seigneur; Benoît Bary; Stéphane Poyet; Gaëtan Touzé (npj Materials Degradation, 2023)
Abstract Coupled Thermal-Hydraulic-Mechanical-Chemical (THMC) approaches may be important for assessing the long-term durability of cementitious materials. We present a multiphysics approach to overcome past limitations of THMC modelling and validate it based on experimental results of accelerated carbonation tests. Our numerical approach rests on a sequential coupling between Hytec and Cast3m. Hytec computes the evolution of hydraulic and mineralogical fields allowing to compute the micromechanical properties (e.g. Young’s modulus). The mineral reactions generate tensile stresses and Cast3M computes the associated strain tensors and the damage evolution represented by the opening or sealing of cracks, impacting subsequent reactive transport processes. Our approach manages to qualitatively represent the crack patterns and non-uniform degradation depths observed on microtomographic images of carbonated cement samples, which can only be explained by the coupled dynamics of chemical and mechanical processes. Our approach can be extended to a wide range of cement-concrete pathologies and contexts.